BIOFUEL CHAIN: DEVELOPMENT, COMPETITIVENESS AND SUSTAINABILITY IN BRAZIL - Kreter, Ana Cecília; Nascimento, Annyeli; Samoggia, Antonella; de Rezende, Gervásio Castro (Informe GEPEC, 2017)
The purpose of this paper is to analyze the Brazilian biofuel chain, according to the Porter’s competitive advantage approach. The Brazilian biofuel policy is worldwide known not only by stimulating its production, but also by granting tax incentives. The current paper highlights how the biofuel policy was developed in Brazilsince the adoption of Proálcool, how this chain works, and how the government coordinates the different production stages. Despite Brazil had gone by different phases, from the full adoption and support by the federal government to the low public incentives, most of the mills kept the productive structure of Proálcool. The results of this study show that the government participation is crucial for the success of the biofuel program. In addition, unlike other nations,Brazilstill has the possibility to increase his production – either through harvest area or through productivity – without environmental damage. Thus,Brazilcould increase its exportation, with relative competitive advantage. Finally, the study results show that, in a medium-term, the biofuel exportation growth cannot affect fuel prices in domestic market, which is another competitive advantage in international market.